Measurement of shear wave speed dispersion in the placenta by transient elastography: A preliminary ex vivo study - Simon, Emmanuel G. (PLoS One, 2018)
BACKGROUND: Placental elasticity may be modified in women with placental insufficiency. Shear wave elastography (SWE) can measure this, using acoustic radiation force, but the safety of its use in pregnant women has not yet been demonstrated. Transient elastography (TE) is a safer alternative, but has not yet been applied to the placenta. Moreover, the dispersion of shear wave speed (SWS) as a function of frequency has received relatively little study for placental tissue, although it might improve the accuracy of biomechanical assessment. OBJECTIVE: To explore the feasibility and reproducibility of TE for placental analysis, to compare the values of SWS and Young’s modulus (YM) from TE and SWE, and to analyze SWS dispersion as a function of frequency ex vivo in normal placentas. MATERIALS AND METHODS: Ten normal placentas were analyzed ex vivo by an Aixplorer ultrasound system as shear waves were generated by a vibrating plate and by using an Aixplorer system. The frequency analysis provided the value of the exponent n from a fractional rheological model applied to the TE method. We calculated intra- and interobserver agreement for SWS and YM with 95% prediction intervals, created Bland-Altman plots with 95% limits of agreement, and estimated the intraclass correlation coefficient (ICC). MAIN RESULTS: The mean SWS was 1.80 m/s +/- 0.28 (standard deviation) with the TE method at 50 Hz and 1.82 m/s +/-0.13 with SWE (P = 0.912). No differences were observed between the central and peripheral regions of placentas with either TE or SWE. With TE, the intraobserver ICC for SWS was 0.68 (0.50–0.82), and the interobserver ICC for SWS 0.65 (0.37–0.85). The mean parameter n obtained from the fractional rheological model was 1.21 +/- 0.12, with variable values of n for any given SWS. CONCLUSIONS: TE is feasible and reproducible on placentas ex vivo. The frequency analysis of SWS provides additional information about placental elasticity and appears to be able to distinguish differences between placental structures.